Teaching and Learning Policy Review in Hong Kong and the U.S. - Lee, Orlan (Education Policy Analysis Archives, 2000)
The Research Assessment Exercises (RAEs) in hugely expanded universities in Britain and Hong Kong attempt mammoth scale ratings of "quality of research." If peer review on that scale is feasible for "quality of research," is it less so for "quality of teaching"? The lessons of the Hong Kong Teaching and Learning Quality Process Reviews (TLQPRs), of recent studies on the influence of grade expectation and workload on student ratings, of attempts to employ agency theory both to improve teaching quality and raise student ratings, and of institutional attempts to refine the peer review process, all suggest that we can "put teaching on the same footing as research" and include professional regard for teaching content and objectives, as well as student ratings of effectiveness and personality appeal, in the process.